The Effect of Application of Science Experiment Methods in Improving Cognitive Early Childhood Age: Literature Review - Derry Heryandini; Dyan Evita Santi; Husni Abdillah (UJoST- Universal Journal of Science and Technology, 2023)
Cognitive development in early childhood is one aspect that needs to be optimized for development because children grow rapidly at an early age. Therefore, the cognitive aspects of early childhood need to get a stimulus so that their development can be optimal. The science experiment is one of the learning methods that can be applied to early childhood. This study aims to discover what science experiments are used in early childhood learning and how they affect cognitive development. The research approach used is qualitative with the type of systematic literature review method PRISMA. The data collection technique is collecting journal articles from previous research per the exclusion and inclusion criteria. The data analysis used is meta-analysis. The results of data analysis show that science experiments applied to early childhood learning include mixing colours and identifying sounds. The results showed that there was an effect of science experiments in improving the cognitive abilities of early childhood.